One-Pot, One-Step Production of Dietary Nucleotides by Magnetic Biocatalysts - del Arco, Jon; Clemente-Suárez, Vicente Javier; Corral, Octavio Jorge; Jordaan, Justin; Hormigo, Daniel; Perona, Almudena; Fernández-Lucas, Jesús; Martínez-Pascual, Sara; Clemente-Suárez, Vicente Javier (Catalysts, 2018)
The enzymatic synthesis of nucleotides offers several advantages over traditional multistep chemical methods, such as stereoselectivity, regioselectivity, enantioselectivity, simple downstream processing, and the use of mild reaction conditions. However, in order to scale up these bioprocesses, several drawbacks, such as the low enzyme stability and recycling, must be considered. Enzyme immobilization may overcome these cost-related problems by enhancing protein stability and facilitating the separation of products. In this regard, tetrameric hypoxanthine-guanine-xanthine phosphoribosyltransferase (HGXPRT) from Thermus thermophilus HB8 was covalently immobilized onto glutaraldehyde-activated MagReSyn (R) Amine magnetic iron oxide porous microparticles (MTtHGXPRT). In this context, two different strategies were followed: (a) an enzyme immobilization through its N-terminus residues at pH 8.5 (derivatives MTtHGXPRT1-3); and (b) a multipoint covalent immobilization through the surface lysine residues at pH 10 (derivatives MTtHGXPRT4-5). The immobilized derivatives of MTtHGXPRT3 (activity 1581 international units per gram of support, IU/g; retained activity 29%) and MTtHGXPRT5 (activity 1108 IU/g; retained activity 23%) displayed the best wet biocatalyst activity, and retained activity values in the enzymatic synthesis of inosine-5'-monophosphate (IMP). In addition, the dependence of the activities and stabilities of both derivatives on pH and temperature was tested, as well as their reusability potential. Taking these results into account, MTtHGXPRT3 was chosen as the best biocatalyst (negligible loss of activity at 60 degrees C during 24 h; reusable up to seven cycles). Finally, as proof of concept, the enzymatic production of dietary nucleotides from high concentrations of low soluble bases was achieved.
Keywords: phosphoribosyltransferases; enzyme immobilization; green process; dietary nucleotides; JCR; Scopus